Usefulness of anti-cyclic citrullinate peptide antibody determination in synovial fluid analysis of patients with rheumatoid arthritis - G. Valesini; R. Scrivo; C. Alessandri; V. Riccieri; A. Spadaro (PAGEPress Publications, 2011)
Objective: To assess the role of anti-cyclic citrullinated peptide (CCP) antibody detection in synovial fluid (SF) of RA patients compared to OA patients. Methods: We evaluated in 25 RA subjects and 14 OA patients, presenting a knee-joint effusion, the main clinical and laboratory parameters including the number of painful and/or swollen joints, Ritchie index, morning stiffness, ESR, CRP and analysis of SF obtained by therapeutic arthrocentesis. IgG anti-CCP (ELISA), rheumatoid factor (RF) and total IgG (nephelometry method) were measured in SF and paired serum samples. Results: We found anti-CCP antibodies and RF in 64% (16/25) and 60% (15/25) of RA sera, respectively; 72% (18/25) of RA patients were positive for anti-CCP antibodies or RF. We found a higher SF/serum ratio for anti-CCP (p<0.004) compared to that for total IgG. The calculation of anti-CCP concentration as IgG anti-CCP (units)/total IgG (g L-1) revealed higher values in SF than in serum (p<0.046) in RA patients. Among these, correlation analysis showed that anti-CCP/total IgG values in SF correlated with the relative concentration of serum anti-CCP/total IgG (rs=0.842; p<0.00001) and serum anti-CCP antibody levels (rs=0.799; p<0.0001). We did not find any correlation between SF anti-CCP levels and the main characteristics of SF as well as the clinical or laboratory parameters. Conclusion: Our study give evidence for a preferential production of anti-CCP antibodies at RA joint level, confirming the pathogenetic role of these autoantibodies. Moreover, SF determination of anti-CCP, corrected for the total amount of the corresponding immunoglobulin, may be helpful as diagnostic tool in selected cases.